Exploring EFL Pre-Service Teachers’ Attitudes of Reflective Practice: A Case Study - M. Yoga Oktama; Endang Fauziati; Dewi Rochsantiningsih (Proceedings Series on Physical & Formal Sciences, 2022)
The research on implementation of three attitudes of reflective practice in the field of pre-service teachers is still rarely written. Thus, this study aimed at exploring pre-service teachers’ attitudes of reflective practice. Designed with case study, this study explored four pre-service teachers at private university in Central Java Indonesia who were enrolled as tutors in an English Tutorial Program of the same university. The data were gathered from pre-service teachers’ reflective journals, interview, and observation. Analyzed using thematic analysis, the findings of this study revealed that all pre-service teachers were captured to possess all virtues of reflective practice namely, open-mindedness, wholeheartedness, and responsibility. This would be a provision for them in developing their professional careers in the future. The implication of this study on language education program is also provided.